Clinical Factors Associated with Intrapartum Presentation Change after Mechanical Cervical Ripening - Wilkie, Gianna; Leung, Katherine; Lauring, Julianne (American Journal of Perinatology, 2023)
Objective The use of mechanical cervical ripening with balloon devices is common during induction of labor; however, there is risk for displacement of the fetal presenting part during its insertion. This study sought to investigate the clinical risk factors associated with an intrapartum presentation change from cephalic to noncephalic presentation after mechanical cervical ripening.Study Design Data were obtained from the Consortium on Safe Labor, a multicenter retrospective study that abstracted detailed labor and delivery information from electronic medical records in 19 hospitals across the United States. All women with fetal cephalic confirmed position on admission undergoing induction of labor with mechanical cervical ripening were included. Women who had a cesarean delivery for noncephalic presentation were compared with women who had a vaginal delivery or cesarean delivery for other indications. Models were adjusted for nulliparity, multiple gestation, and gestational age.Results A total of 3,462 women met inclusion criteria, with 1.3% (n = 46) having an intrapartum presentation change from cephalic to noncephalic presentation after mechanical cervical ripening. Those who had a cesarean delivery for an intrapartum presentation change were more likely to be nulliparous (82.6 vs. 65.4%, p = 0.01), less than 34 weeks' gestation (6.5 vs. 1.3%, p = 0.02), and have twins (6.5 vs. 1.2%, p = 0.02). In adjusted analysis, twins were associated with an increased odds of cesarean delivery for intrapartum presentation change (adjusted odds ratio [aOR]: 4.43; 95% confidence interval [CI]: 1.25–15.77), whereas multiparity reduced the odds (aOR: 0.38; 95% CI: 0.17–0.82).Conclusion Nulliparity and multifetal gestation are associated with a cesarean delivery for an intrapartum presentation change after mechanical cervical ripening.Key Points
Keywords: intrapartum presentation change; mechanical cervical ripening; cervical balloon; cesarean delivery